2023
DOI: 10.1021/acs.oprd.3c00028
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Enantiomeric Excess Measurements of Enantioisotopomers by Molecular Rotational Resonance Spectroscopy

Abstract: Recent work in drug discovery has shown that selectively deuterated small molecules can improve the safety and efficacy for active pharmaceutical ingredients. The advantages derive from changes in metabolism resulting from the kinetic isotope effect when deuterium is substituted for a hydrogen atom at a structural position where rate limiting C–H bond breaking occurs. This application has pushed the development of precision deuteration strategies in synthetic chemistry that can install deuterium atoms with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Similarly low ee has been found for three reaction products containing nitrogen heterocycles (ethylpyridine- d1 , 8-ethylquinoline- d1 , and 2-(4-ethylphenyl)pyridine- d1 ). 25 There is an interesting correlation that all low ee substrates have strong hydrogen bond acceptor positions where the chiral tag complex with TFIP prefers to attach via formation of a classical hydrogen bond ( Figure 7 ) instead of through interaction with the aromatic ring ( Figures 1 and 11 ). Future synthetic methodology development will explore ways to achieve high enantioselectivity in these substrates with hydrogen bond acceptor sites.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly low ee has been found for three reaction products containing nitrogen heterocycles (ethylpyridine- d1 , 8-ethylquinoline- d1 , and 2-(4-ethylphenyl)pyridine- d1 ). 25 There is an interesting correlation that all low ee substrates have strong hydrogen bond acceptor positions where the chiral tag complex with TFIP prefers to attach via formation of a classical hydrogen bond ( Figure 7 ) instead of through interaction with the aromatic ring ( Figures 1 and 11 ). Future synthetic methodology development will explore ways to achieve high enantioselectivity in these substrates with hydrogen bond acceptor sites.…”
Section: Resultsmentioning
confidence: 99%
“…The rms rotational constant error for the scaled rotational constants used to assign the homochiral and heterochiral tag complexes to establish the absolute configuration is about thirty times smaller, 0.030%. Previous work demonstrated that chiral tag rotational spectroscopy provides high-speed ee measurement capabilities 25 and that MRR spectroscopy is a quantitative technique for measuring both the isotopolog and isotopomer distributions in deuterated molecules. 10 MRR spectroscopy delivers the full analysis capabilities required to support the development of synthetic chemistry approaches to precision deuteration chemistry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 The ee% also indicates how much of a drug is available in a therapeutic dose relative to the theoretical optimal dose. 10 Because living creatures are so sensitive to introduced molecules’ chirality, recognizing and quantitatively sensing chiral compounds is of great medical and biological significance.…”
Section: Introductionmentioning
confidence: 99%